Un beso en mi mano - Penn, Audrey, 1947-; Harper, Ruth E.; Leak, Nancy M. (New York : Scholastic, 2002)
When Chester the raccoon is reluctant to go to kindergarten for the first time, his mother teaches him a secret way to carry her love with him.
"This edition is only available for distribution through the school market"--P. [4] of cover.
Accelerated Reader AR
Keywords: Separation anxiety -- Juvenile fiction; Mothers and sons -- Juvenile fiction; Procyon -- Juvenile fiction; Raccoon -- Juvenile fiction; Forest animals -- Juvenile fiction; Kindergarten -- Juvenile fiction; Schools -- Juvenile fiction; Spanish language materials -- Juvenile fiction